Multiplex real-time PCR for detection of qac A/B and smr genes in Gram-positive bacteria - Svetlana N. Kovalchuk; Anna L. Arkhipova; Svetlana Yu. Kovylkova; Elena N. Ilina; Lyudmila S. Fedorova (Журнал микробиологии, эпидемиологии и иммунобиологии)
Background. Disinfectants are effective means of non-specific prevention of infections associated with the provision of medical care. Violation of disinfectant use regimes leads to the formation of microorganism resistance to them. To monitor the spread of clinically significant microorganisms resistant to disinfectants, the development of methods for their detection, including molecular genetic methods, remains relevant.